EFEKTIVITAS MODEL PEMBELAJARAN PEROLEHAN KONSEP (CONCEPT ATTAINMENT) TERHADAP KEMAMPUAN MENEMUKAN UNSUR-UNSUR INTRINSIK CERPEN “KISAH DI KANTOR POS” KARYA MUHAMMAD ALI OLEH SISWA KELAS IX SMP N 4 TARUTUNG TAHUN PEMBELAJARAN 2012/2013 - FITRIA HUTAGALUNG (Kode : Jurnal Bahasa, 2014)
This research aims to determine the effectivity of conceptattainment model in learning to discover short stories’ intrinsicelements of the ninth grade students of SMP N 4 Tarutung, inacademic year 2012/2013. The population of this research was asmany as 120. The sample was taken randomly as many as 40students, 20 students for experimental class and 20 other studentsfor control class. The method of this research was the experimentalmethod. The instrument conducted was to discover intrinsicelements of short stories in post-test form. The average of theexperimental class was 75.25, while the average of control classwas 65.25. Hence, it can be said that the score in finding intrinsicelements of experimental class was higher than contol class’ score.Hypothesis testing was conducted by using ????????????????????, from thecalculation of hypothesis testing, it was found that the score of???????????????????????? was 4.61, furthermore it was consultated by table withsignifican level 5% = 1.68 and in level 1% = 2.42, with df level =(20+20) – 2 = 38. In table t with df level = 38, it was found that???????????????????????? in significan level the hypothesis was effective, because???????????????????????? <????????????????????????>???????????????????????? namely, (1.68<4.61>2.42) thus, thealternative hypothesis (Ha) was accepted. Therefore, it is concludedthat concept attainment model in learning was effectively used infinding intinsic elements of short stories by the ninth grade of SMPN 4 Tarutung, academic year 2012/2013.Keywords: effectivity, concept attaiment model, intrinsic elements,